Night-time movement of fish in coastal waters of Terengganu - Ibrahim, Sakri; Ambak, Mohd Azmi; Kawamura, Gunzo (Universiti Putra Malaysia Press, 1997)
The night-time movement pattern of 15 fish species in Terengganu waters was inferred from the driftnet catch obtained from experimental driftnetting in two monsoon seasons. Nets shot perpendicular to the coast drifted northward or southward parallel to the coast at 0.33-1. 78 km/h. Thirteen out of 15 species caught were enmeshed significantly against the current. Observations on gonad development of some migratory pelagic species showed that these species were on spawning migration to nearl7y known spawning areas. Daytime and long-term movement patterns remain unknown.